A new fouling Hydroides (Annelida, Sabellida, Serpulidae) from southern Gulf of California. (8th June 2015) - Tovar-Hernández, María Ana; Villalobos-Guerrero, Tulio F.; Kupriyanova, Elena K.; Sun, Yanan
Abstract : Members of the tubicolous polychaete family Serpulidae constitute one of the most important groups of marine fouling biota. This paper describes a new species of the serpulid genus Hydroides from dock fouling at Mazatlán (southern Gulf of California), providing information about live colouration and reproductive features. Hydroides dolabrus sp. nov. belongs to a subgroup of species in which verticil spines are equal in size and shape, lack both external and lateral spinules, but have various modifications to their tips. However, Hydroides dolabrus sp. nov. is distinct in having tips of verticil spines pickaxe-shaped, with asymmetrical triangular radially orientated projections: the internal projections are short and point inward the verticil centre, while longer external projections point outward the verticil centre. Like all species of the genus, H. dolabrus sp. nov. is a gonochoristic broadcast spawner lacking sexual dimorphism. A phylogenetic analysis of Hydroides based on COI, 18S and cyt b sequence data reveals that H. dolabrus sp. nov. is genetically distinct from other species of Hydroides for which sequence data are available. The new species is the 11th in the genus described from Mexican waters.